2007
DOI: 10.1017/s0024282907006937
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive strategy and the compositional dynamics of crustose lichen communities on aspen (Populus tremula L.) in Scotland

Abstract: Ecological studies are essential in understanding the response of crustose lichens to habitat dynamics and developing effective conservation strategy. While the combined response of individual crustose species within a community will be tremendously complex, the overall result of individualistic change can be simplified using trait-based analyses. In this paper we examine the response of crustose species with contrasting reproductive traits (predominantly sexual vs asexual reproduction) and which occur within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 39 publications
1
29
1
1
Order By: Relevance
“…increased with the circumference of tree. Still, the effects of tree ageing and/or tree size on bark acidity are hard to generalize as reverse effects have been observed depending on analysed tree species (Bates and Brown 1981;Bates 1992;Hyvärinen et al 1992;Ellis and Coppins 2007b). We also noted that bark pH is higher in the case of trees with a more extensive cover of bryophytes.…”
Section: Discussionmentioning
confidence: 69%
“…increased with the circumference of tree. Still, the effects of tree ageing and/or tree size on bark acidity are hard to generalize as reverse effects have been observed depending on analysed tree species (Bates and Brown 1981;Bates 1992;Hyvärinen et al 1992;Ellis and Coppins 2007b). We also noted that bark pH is higher in the case of trees with a more extensive cover of bryophytes.…”
Section: Discussionmentioning
confidence: 69%
“…In Parmeliaceae (heteromous thallus), Parmelia (sensu lato) species from personal observation are usually vegetatively reproducing on the trunks of trees and most of the spore reproducing species occurring on twigs. Ellis and Coppins (2007) have shown that the mix of crustose lichen species occurring on aspen bark are more likely to be spore reproducing on young twig bark but there is a vegetatively reproducing mix on older branch bark with a clear trend from one to the other as the bark ages. The hyphae from germinating lichen spores presumably find endophloeodal Trebouxia cells on, or, possibly more likely, in the dead epidermal cells which might be an enclosed habitat similar to that within a lichen thallus.…”
Section: Questions About Photobiontsmentioning
confidence: 99%
“…The rough bark is more efficient surface structure to grasp the water and moisture from rain and dew. In the past, [21] also found that it is often visually obvious that colonization is more extensive on rough and porous surfaces than smooth, non-porous ones. Lichen studies also showed the rough bark also provides a greater opportunity for thallus fragments of lichens to embed in its surface [22].…”
Section: Discussionmentioning
confidence: 99%